ESTUDO DO EFEITO GENÉTICO DOS PAIS (TOUROS) NO DESEMPENHO PRODUTIVO DE BEZERROS NELORE (BOS TAURUS INDICUS) NO REBANHO UEMS - LECA FERREIRA, Luana; FERRAZ, André Luiz Julien; MORAIS, Rafael Braga de; BARONI, Guilherme da Silva; ROJAS, Luiz Eduardo Souza (ANAIS DO ENIC, 2025)
-